Speech by Y.A.B. Ketua Menteri on the occasion of the launching of the Westland Rukun Tetangga Scheme to be held at the Rubber Trade Association Building,Anson Road on 1st June 1976 at 6.15 p.m. - Lim, Chong Eu (1976)
It gives me great pleasure to be present with you today on the occasion of the Launching of the 4th Rukun Tetangga sector in the State of Penang.